Positive solutions for a system of Riemann–Liouville fractional boundary value problems with p-Laplacian operators - Tudorache, Alexandru; Luca, Rodica (Advances in difference equations, 2020)
We study the existence and nonexistence of positive solutions for a system of Riemann–Liouville fractional differential equations with p -Laplacian operators, nonnegative nonlinearities and positive parameters, subject to coupled nonlocal boundary conditions which contain Riemann–Stieltjes integrals and various fractional derivatives. We use the Guo–Krasnosel’skii fixed point theorem in the proof of the main existence results.